Staurosporine induces apoptosis in pancreatic carcinoma cells PaTu 8988t and Panc-1 via the intrinsic signaling pathway - Malsy, Manuela (Eur J Med Res, 2019)
BACKGROUND: Cancer, one of the leading causes of death worldwide, develops when the normal balance between mitosis and apoptosis is disrupted. The subsequently increased proliferation rate or decreased apoptosis rate of cells leads to uncontrolled cellular growth. Thus, the current aim of cancer research is to increase the apoptosis rate in tumor cells—while limiting the concurrent death of healthy cells—and to induce controlled apoptosis in abnormal cells. Staurosporine is a very potent inducer of apoptosis because it inhibits many different kinases. So far, many different kinase pathways of staurosporine-induced apoptosis have been discussed for various tumor entities. AIMS: To identify the effect of staurosporine in pancreatic and colorectal carcinoma cells and its apoptosis-inducing signaling pathway. METHODS: The apoptosis rate in pancreatic and colorectal carcinoma cells was analyzed by annexin V staining after staurosporine administration. Staurosporine stimulation and its effects on the expression of Bcl2, BAX, Bad, caspase-8, and caspase-9 were investigated with immunoblot. RESULTS: Staurosporine significantly increased apoptosis in pancreatic carcinoma cells. Western blot analysis showed activation of caspase-9 in PaTu 8988t and Panc-1 cells with 1 µM staurosporine. In addition, expression of Bcl2 and Bad was decreased in PaTu 8988t cells. In colorectal carcinoma cells SW 480, staurosporine stimulation did not induce apoptosis. CONCLUSION: Modern therapeutic strategies for tumor diseases target the efficient modulation of specific signaling and transcription pathways. In this respect, the therapeutic potential of protein kinase inhibitors has been repeatedly discussed. Our study showed that staurosporine induces apoptosis in pancreatic carcinoma cells via the intrinsic signaling pathway. Thus, staurosporine is a suitable positive control for in vitro apoptosis tests for the pancreatic cancer cell lines PaTu 8988t and Panc-1. Further clinical studies should analyze the impact of this finding on cancer treatment.